2010
DOI: 10.1007/s12264-010-0933-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of M4 muscarinic acetylcholine receptors by interacting proteins

Abstract: Protein-protein interactions represent an important mechanism for posttranslational modifications of protein expression and function. In brain cells, surface-expressed and membrane-bound neurotransmitter receptors are common proteins that undergo dynamic protein-protein interactions between their intracellular domains and submembranous regulatory proteins. Recently, the Gαi/o-coupled muscarinic M4 receptor (M4R) has been revealed to be one of these receptors. Through direct interaction with the intracellular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Activation of the Gq-coupled M1 receptor is typically expected to increase pCREB levels through calcium-dependent activation of PKC signaling pathways . By contrast, activation of the Gi/o-coupled M4 receptors is expected to decrease pCREB levels by reducing cAMP production . Surprisingly, we found that xanomeline produced differential pCREB responses in all three brain regions under investigation (Figure A).…”
Section: Resultsmentioning
confidence: 69%
“…Activation of the Gq-coupled M1 receptor is typically expected to increase pCREB levels through calcium-dependent activation of PKC signaling pathways . By contrast, activation of the Gi/o-coupled M4 receptors is expected to decrease pCREB levels by reducing cAMP production . Surprisingly, we found that xanomeline produced differential pCREB responses in all three brain regions under investigation (Figure A).…”
Section: Resultsmentioning
confidence: 69%
“…Our gene expression analysis reveals potential molecular abnormalities in both striatonigral and striatopallidal pathways. On one hand, low mRNA levels of Camk2a and chrm4 (coding for the alpha isoform of the calcium/calmodulin-dependent protein kinase II-a critical effector of muscarinic receptor 4-and the cholinergic muscarinic receptor 4, respectively), and high mRNA levels of grin2b (NR2B subunit of NMDA glutamate receptors) may potentiate the striatonigral output (Gomeza et al, 1999;Guo et al, 2010;Jocoy et al, 2011;Tzavara et al, 2004). On the other hand, increased expression of Grm4 (metabotropic glutamate receptors mGluR4) and Pdyn (dynorphin and related peptides), and decreased expression of Tac1 (substance P) and Gpr6 (Gprotein-coupled receptor GPR6) would rather blunt striatopallidal activity (Govindaiah et al, 2010;Hopkins et al, 2009;Lobo et al, 2007;Perreault et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transcriptional regulations of several genes in the CPu were coherent with behavioral data pointing to facilitated D1R-and blunted D2R-bearing MSN activity in DOR null mice. Indeed, low mRNA levels of Camk2 and chrm4 (coding for the alpha isoform of the calcium/calmodulin-dependent protein kinase II and mAchR4, respectively) and high mRNA levels of grin2b (NR2B subunit of NMDA glutamate receptors) could facilitatestriatonigral outputs in mutants (Gomeza et al 1999;Guo et al 2010;Jocoy et al 2011;Tzavara et al 2004). In contrast, increased expression of Grm4 (metabotropic glutamate receptor mGluR4) and Pdyn (prodynorphin) and decreased expression of Tac1 (substance P) and Gpr6 (GPR6) would rather inhibitstriatopallidal activity (Govindaiah et al 2010;Hopkins et al 2009;Lobo et al 2007;Perreault et al 2007).…”
Section: Dors and Striatal Gene Expressionmentioning
confidence: 99%